Smith and Aitkenhead's Textbook of anaesthesia - Smith, G. (Graham); Aitkenhead, A.R. (Alan R.); Moppett, Iain K.; Thompson, Jonathan P. (Churchill Livingstone/Elsevier, 2013)
A practical guide for anaesthetists and other health care professionals involved in the perioperative period. This sixth edition has been thoroughly updated and reorganised to reflect current anaesthetic practice and the basic sciences that directly underpin it. The inclusion of several new chapters continues to ensure complete coverage of key and evolving areas and new, experienced authors also add a fresh perspective to this edition.